Gestión publicitaria en el Almacén “Créditos López” en la parroquia San Juan-Cantón Puebloviejo periodo 2021. - Vargas Angulo, Leydi Omaira (2022)
The main objective of this case study entitled Advertising management in the "Créditos López" warehouse is to analyze the advertising management of the "CRÉDITOS LÓPEZ" warehouse located in the San Juan-Cantón Puebloviejo parish, evaluating the marketing strategies applied in the commercial, so that in this way implement tactics that are effective for which it can be recognized by the residents of the parish and in the surrounding sectors through advertising so that it has customer acceptance and be recognized in the market. With this case study, its purpose is to find advertising methods to increase sales in the commercial establishment, which guarantees the effective management of commercial resources as the main source of economic growth of the company, taking into account the improvement of quality in the offer of products, therefore, face the difficulties that the competitive market presents and thus be able to stay in the user's mind for a long time and achieve the loyalty of a greater number of consumers. The method that was used in this work was the root cause because it allowed to detect the shortcomings that the company has and correct them through advertising strategies, which will be reflected by increasing sales; the technique that was used is the survey applied to the clients and the interview addressed to the owner of the company and the instrument was a questionnaire of 11 questions and a questionnaire of 8 questions. The line of research related to this case study is the line of research: Financial, administrative, audit and control management and is part of the subline: Marketing and commercialization.